Use of an acoustic wave sensor to follow lead absorption by porcine skin - Veríssimo, Marta I. S. (2008)
A new acoustic wave sensor capable of detecting and quantifying lead is presented, and fully characterized in terms of sensitivity, selectivity, and linear calibration range. The sensor was used to quantify lead absorption by pig stratum corneum and to follow in real time, both the absorption and desorption of lead by the skin. Values of lead absorption of 29.6 mg Pb2+/g of stratum corneum were obtained. Lead in solution was also quantified by atomic absorption spectrometry (AAS). The results obtained by both methods, AAS and the sensor, were compared and no statistical differences in the accuracy and precision of the results were found.